Przyszedłem rozłączyć... Jana Dobraczyńskiego jako obraz „świętości bezwiednej” - Mazan-Mazurkiewicz, Alicja (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2012)
The works by Dobraczyński, once a very popular Polish catholic author have become almost completely forgotten. There are only two novels still known among readers: Listy Nikodema i Cień Ojca. The aim of this article is to remind one of the forgotten novels Przyszedłem rozłączyć... which presents the hagiographic trend, especially important in Dobraczyński’s works. Despite some artistic inadequacies, the novel still seems interesting because of the depiction of holiness and problems emerging from it, which are dubious, although the author’s overall tendency was to be explicit.